Spontaneous Neonatal Gastric Perforation: About Two Cases Treated with Success in Cotonou - GBENOU, ANTOINE SÉRAPHIN; TCHIAKPE-ENIALOKO, NICOLE (My University, 2020)
Neonatal gastric perforation is rare with a serious prognosis. Over a period of 10 years we had two cases successfully treated in our departments. Cases: It was a girl and a boy, vaginely delivered in the same year. The pregnancy was well followed in the first case and badly in the second. APGAR score at birth, at 2700 g girl was 10-10-10, and at 2900 g boy at 7-7-8 after resuscitation. On admission, newborns were cyanotic, tachycardic and tachypnotic; there was abdominal distension with diffuse abdominal tympanism, occurring on the second day, and scrotal swelling in addition for the boy. The abdominal X-rays objectified a massive pneumoperitoneum in the shape of a “saddle horse”. Laparotomy found gastric perforation in the area of parietal hypoplasia in both cases. An excision suture had been performed. The postoperative course was simple. Conclusion: Spontaneous neonatal gastric perforation is rare. Early diagnosis and management had resulted in a favourable outcome of the cases.
Keywords: Gastric perforation; Newborn; Treatment; Benin